Learning and Education in Developing Countries: Research and Policy for the Post-2015 UN Development Goals - Wagner, Daniel A.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
This comprehensive and up-to-date review of learning and educational quality in developing countries, written by 16 highly knowledgeable specialists from around the world, provides policymakers and researchers accessible perspectives with the Millennium Development Goals in mind.
Keywords: Science; Science, general